The Topography and Physical Activity as Determinant Factor of Grade Hypertension in Patients with Primary Hypertension - Robby, Krish Naufal Anugrah; Soesetijo, FX. Ady; Marchianti, Ancah Caesarina Novi (Health Notions, 2018)
Primary hypertension is a causing factor of cardiovascular disease mortality. Patient with primary hypertension having high grade hypertension will cause various dangerous diseases if it is not performed further countermeasures. Consequently, it is necessary to prevent the increase of grade hypertension or blood pressure by analyzing grade hypertension risk factor. This study was quantitative research with cross sectional design method. The samples in this study were 346 respondents taken by consecutive sampling. Partial Least Square (PLS) with SmartPLS (v. 3.2.7) application software was used as to analyze the data. Results shows that there is a physical activity effect on grade hypertension, with the value of path coefficient by -0.564 of t statistic 16.48 (t statistic > t table significance by 1.96). Based on the result of the study, there is a topography effect on grade hypertension, with the value of path coefficient by 0.412 of t statistic 8.690 (t statistic > t table significance by 1.96). Physical activity affects grade hypertension. The better the physical activity, the better the way to prevent a blood pressure increase mainly systolic blood pressure. The high topography can lead to increase grade hypertension in the primary hypertension patient, therefore, lifestyle and topographic effect should also be considered for people with primary hypertension mainly for non-native people who have not experienced acclimatization. Keywords: Primary hypertension, Topography, Physical activity, Grade hypertension